Interventional Radiology Cases. - Covey, Anne M. (Oxford University Press, USA, 2014)
In 104 cases featuring over 500, high-quality images, Interventional Radiology Cases is a thorough and accessible review of the interventional procedures that radiology residents are expected to be familiar with upon completion of residency and general radiologists need to know for recertification examinations. The cases present both benign and malignant conditions and all pertinent imaging modalities incorporated including: CT, MR, PET, fluoroscopy, and ultrasound. Part of the Cases in Radiology series, this book follows the easy-to-use format of question and answer in which the patient histo.